Psychosocial risk factors associated to cardiovascular disease in college students - Figueroa López, Carlos; Alcocer Díaz Barreiro, Luis; Ramos del Rio, Bertha (Anales de Psicología / Annals of Psychology, 2011)
The goal was to determine the relationship among cardiovascular risk factors with cardiovascular reactivity and recovery of blood pressure and heart rate on normotensive college students. 110 students were divided in: a) cases (N=52) with positive familiar antecedent of hypertension, and b) controls (N=58) with negative familiar antecedent of hypertension. Familiar antecedent of diabetes, high intake of fat food, and stress were found in both groups. Cases group showed ambition, impulsiveness and competitiveness. Multiple linear regression analysis of the systolic and diastolic blood pressure and heart rate reactivity to the emotional stressor indicated an association with sedentary, high intake of fat food and stress. Cardiovascular risk factors in college students indicate that it is a vulnerable group to suffer from cardiovascular diseases.